Stimulation of Innate and Adaptive Immunity by Using Filamentous Bacteriophage fd Targeted to DEC-205. (26th August 2015) - D'Apice, Luciana; Costa, Valerio; Sartorius, Rossella; Trovato, Maria; Aprile, Marianna; De Berardinis, Piergiuseppe
Abstract : The filamentous bacteriophage fd, codisplaying antigenic determinants and a single chain antibody fragment directed against the dendritic cell receptor DEC-205, is a promising vaccine candidate for its safety and its ability to elicit innate and adaptive immune response in absence of adjuvants. By using a system vaccinology approach based on RNA-Sequencing (RNA-Seq) analysis, we describe a relevant gene modulation in dendritic cells pulsed with anti-DEC-205 bacteriophages fd. RNA-Seq data analysis indicates that the bacteriophage fd virions are sensed as a pathogen by dendritic cells; they activate the danger receptors that trigger an innate immune response and thus confer a strong adjuvanticity that is needed to obtain a long-lasting adaptive immune response.